2000
DOI: 10.1038/35002533
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the surface energy of liquid interfaces at short length scales

Abstract: Liquid-vapour interfaces, particularly those involving water, are common in both natural and artificial environments. They were first described as regions of continuous variation of density, caused by density fluctuations within the bulk phases. In contrast, the more recent capillary-wave models assumes a step-like local density profile across the liquid-vapour interface, whose width is the result of the propagation of thermally excited capillary waves. The model has been validated for length scales of tenths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
241
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(258 citation statements)
references
References 23 publications
14
241
3
Order By: Relevance
“…Although definitive explanation may not be provided at this time, it is conceivable that such interactions could be propagated by thermal capillary waves (CW), which are powered by the thermal surroundings and span broad frequency ω CW and wavelength λ CW domains. [71][72][73][74][75][76] Recent simulations have shown that anions specifically bias surface height fluctuations several molecular diameters away by pinning thermal capillary waves. 77 The preceding dipole moments of water molecules bound to interfacial anions that, in contrast with those bound to cations, generate oscillating fields parallel to the surface might be an essential feature of the propagation mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Although definitive explanation may not be provided at this time, it is conceivable that such interactions could be propagated by thermal capillary waves (CW), which are powered by the thermal surroundings and span broad frequency ω CW and wavelength λ CW domains. [71][72][73][74][75][76] Recent simulations have shown that anions specifically bias surface height fluctuations several molecular diameters away by pinning thermal capillary waves. 77 The preceding dipole moments of water molecules bound to interfacial anions that, in contrast with those bound to cations, generate oscillating fields parallel to the surface might be an essential feature of the propagation mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…For this analysis, wetting contact angles were assumed based on the observations of Rossi et al [219] and Kim et al [220], and continuum approximations for capillary dynamics [220], surface tension [221], and viscous drag [222] were shown to be justified. Properties were obtained as a function of nanowire diameters and number densities consistent with typical fabrication processes [223][224][225].…”
Section: Assessment and Design Of Nanostructured Wicksmentioning
confidence: 99%
“…This influx then balances the gas outflux from the nanobubble, leading to bubble stability. Other explanations include possible lowering of surface tension for large curvatures on small scales [23,24], the oversaturation of liquid with gas in the vicinity of nanobubbles [15], the effect of induced charges in the Debye layer developed around the bubble interface [25], etc. A recent study by Borkent et al [8] suggests that contaminations also have a strong effect on the contact angle.…”
Section: Introductionmentioning
confidence: 99%